2018
DOI: 10.1111/1462-2920.14340
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting distributions of bacteriophages and eukaryotic viruses from contaminated coastal sediments

Abstract: Viruses are ubiquitous, abundant and play an important role in all ecosystems. Here, we advance understanding of coastal sediment viruses by exploring links in the composition and abundance of sediment viromes to environmental stressors and sediment bacterial communities. We collected sediment from contaminated and reference sites in Sydney Harbour and used metagenomics to analyse viral community composition. The proportion of phages at contaminated sites was significantly greater than phages at reference site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…However, identification of viral sequences from environmental metagenomes remains a non‐trivial task because of the limited size of the available databases of known viral genomes and the lack of sufficiently powerful and reliable bioinformatics tools to detect viral sequences from metagenomes. Several viromic studies revealed the unique diversity of viruses in marine sediments (Yoshida et al ., 2013; 2018; He et al ., 2017; Nguyen et al ., 2017; Lachnit et al ., 2019). However, most of these studies were performed on enriched VLPs from sediment samples and, therefore, might not present a complete picture of viral diversity in the sediments because of the difficulties in releasing VLPs from the samples and the inability of detecting viral sequences integrated in the host genomes in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, identification of viral sequences from environmental metagenomes remains a non‐trivial task because of the limited size of the available databases of known viral genomes and the lack of sufficiently powerful and reliable bioinformatics tools to detect viral sequences from metagenomes. Several viromic studies revealed the unique diversity of viruses in marine sediments (Yoshida et al ., 2013; 2018; He et al ., 2017; Nguyen et al ., 2017; Lachnit et al ., 2019). However, most of these studies were performed on enriched VLPs from sediment samples and, therefore, might not present a complete picture of viral diversity in the sediments because of the difficulties in releasing VLPs from the samples and the inability of detecting viral sequences integrated in the host genomes in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of phages onto flagella was examined under TEM after negative stain with 2% (w/v) aqueous uranyl acetate. 40 Given that the flagella can be the receptor for some phages specifically to attach to their hosts, 41,42 the flagella-attached phages were subject to double-layer plaque assays seeded with B. cereus to assess the infectivity of the flagella-enriched fraction toward B. cereus.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The phage concentrate and flagella solution were mixed and incubated at 20 °C for 24 h. The mixture was filtered through 0.2 μm Anopore membranes (GEwhatman, 6809-6022, U.K.), and then the flagella-attached phages were collected on the membrane surface by flushing the filter membrane repeatedly with 1 mL of the saline solution (0.9% NaCl). The attachment of phages onto flagella was examined under TEM after negative stain with 2% (w/v) aqueous uranyl acetate . Given that the flagella can be the receptor for some phages specifically to attach to their hosts, , the flagella-attached phages were subject to double-layer plaque assays seeded with B.…”
Section: Methodsmentioning
confidence: 99%